TERRORIST ACTIVITIES OF YEMEN'S HOUTHIS IN RESPONSE TO ISRAEL'S MILITARY ACTIONS AND CONSEQUENCES FOR INTERNATIONAL SECURITY AND TRADE - Rašović, Stefan; Slavkovic, Nikola (Political Review, 2025)
The Houthis (Ansar Allah) are a militant movement that cultivates a Zaydi form of Shiism and originate from Saad, a province in northern Yemen. Since 2014, they have been engaged in a civil war, fighting for supremacy in Yemen. The Hamas attack on Israel on October 7, 2023, marked the beginning of a new war in the Middle East. The Houthis immediately supported Hamas after the attack, and following Israel’s retaliation and the launch of its military operation, they announced that they would target military and commercial vessels linked to Israel in any way, sailing through the Gulf of Aden and the Red Sea. The fundamental assumption of this paper is that the actions of the Houthis constitute acts of terrorism, with consequences for international security and trade being far-reaching. The aim of this paper is to analyze the Houthis activities, as their response to Israel's military actions, and with the aim of providing support to the people of Palestine, while noting that, as of January 2024, they have been characterized as a special designed terrorist by the United States. In the first part of the paper, a conceptual definition of terrorism and maritime terrorism will be given, while in the second part the emphasis will be on explaining the origin of this movement, their participation in the civil war, as well as answering the question of whether they are terrorists or rebels. The third part of the paper will analyze the reaction of the Houthis to Israel's military actions, which are a consequence of the attacks by Hamas, as well as the chronology and description of their attacks since November 2023. The last part of the paper will show the consequences for international security and trade, as well as the way the world responded to the actions of the Houthis, in the form of the creation of two operations, Prosperity Guardian and Aspides.
Keywords: Houthis; terrorism; The Red Sea; The Gulf of Aden; sailing; international security; trade